The microvascular reconstruction in children with maxillofacial defects: A Systematic Review - Violetti Valentin; Ratna Rayeni Natasha Roosseno (Intisari Sains Medis, 2022)
Background: Facial bones trauma in the pediatric population is linked to severe damage and impairment, particularly in maxillofacial, particularly in area. In addition, reconstruction of maxillofacial in pediatric patients has some unique considerations. Therefore, this study described the effectiveness of microvascular reconstruction in children with maxillofacial defects.Methods: The relevant literature from PubMed and Science Direct databases. The strategic search is using the keywords such as "Pediatric" OR "Children" OR "Under-eighteen years" AND "microvascular reconstruction" OR "microvascular surgery" AND "maxillofacial defect". We used a PRISMA method to the selection of those articles. The inclusion criteria were related to microvascular reconstruction in children with maxillofacial defects from 2000-2021.Result: Total of six studies entries with inclusion criteria. These studies show that most free flaps or microvascular reconstruction procedures carried on pediatric patients to resolve maxillofacial defects gave successful functional, and clinical outcomes. In addition, a few complications, mainly infections, occurred following the surgery, however successfully managed with antibiotics.Conclusion: A microvascular reconstruction is a good option for maxillofacial defects reconstruction in pediatric patients due to a shorter surgical time and faster recovery.